FORMULASI STRATEGI UNTUK MENCAPAI KEUNGGULAN BERSAING DI CARLOGISTIK - , Aziza Leila Komala ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Competition in the world of logistics in the world and in Indonesia are getting tighter, coupled with difficult economic conditions to be ascertained, demanding every logistics company to work more effectively and efficiently. CARLogistik is one of the leading local logistics company in Indonesia, which has existed for more than 28 years, but unfortunately in the last two years the company's revenue performance is low while costs to be incurred is not reduced and even in some cases even increased. From the results of the analysis, it is concluded that at present, CARLogistik is in a state of crisis, but still has some strengths and resources that have not been put to good use to improve the competitiveness, efficiency and productivity. Therefore, the formulation of appropriate strategies can reduce ongoing costs, support improved performance and overall competitiveness of CARLogistik so as to increase the income of the company and make the company excel in the competition in the logistics industry today. In this study, a tool used for strategy formulation is a SWOT matrix of internal and external matrix of CARLogistik, using input from internal factors evaluation matrix, matrix evaluation of external factors and competitive profile matrix.